The effect of advanced recovery room care on postoperative outcomes in moderate‐risk surgical patients: a multicentre feasibility study. (7th October 2020) - Ludbrook, G.; Lloyd, C.; Story, D.; Maddern, G.; Riedel, B.; Richardson, I.; Scott, D.; Louise, J.; Edwards, S.
Summary: Postoperative complications are common and may be under‐recognised. It has been suggested that enhanced postoperative care in the recovery room may reduce in‐hospital complications in moderate‐ and high‐risk surgical patients. We investigated the feasibility of providing advanced recovery room care for 12–18 h postoperatively in the post‐anaesthesia care unit. The primary hypothesis was that a clinical trial of advanced recovery room care was feasible. The secondary hypothesis was that this model may have a sustained impact on postoperative in‐hospital and post‐discharge events. This was a multicentre, prospective, feasibility before‐and‐after trial of moderate‐risk patients (predicted 30‐day mortality of 1–4%) undergoing non‐cardiac surgery and who were scheduled for postoperative ward care. Patients were managed using defined assessment checklists and goals of care in an advanced recovery room care setting in the immediate postoperative period. This utilised existing post‐anaesthesia care unit infrastructure and staffing, but extended care until the morning of the first postoperative day. The advanced recovery room care trial was deemed feasible, as defined by the recruitment and per protocol management of > 120 patients. However, in a specialised cancer centre, recruitment was slow due to low rates of eligibility according to narrow inclusion criteria. At a rural site, advanced recovery room care could not be commenced due to logistical issues in establishing a new model of care. A definitive randomised controlled trial of advanced recovery room care appears feasible and, based on the indicative data on outcomes, we believe this is warranted.